Technical advancement and the stimulation of companies innovation activity by business support organisations in developed regions - Gorączkowska, Jadwiga (Ekonomia i Prawo. Economics and Law, 2017)
Motivation: Currently, an increasing role in achieving the competitive advantage is attributed to knowledge and its conversion to new products and services. For this reason, institutions have been set up, which are designed to stimulate the innovation activity in the economy. Their development was initiated in developed countries, and then moved to the developing countries. Aim: The article presented the influence of business support institution, which most frequently occur in the Polish reality, i.e., technological parks, technological incubators, academic business incubators, technology transfer centers, business angel networks, local or regional loan funds, credit guarantee funds and training-advisory centers for the innovation activity of industrial companies with consideration of the manufacturing techniques used by them in the developed regions of Poland, i.e., from the Lower Silesia, Silesia and Greater Poland. Results: Innovation attributes were distinguished according to the standards of studying the innovation activity contained in the Oslo methodology. For the conduct of analyses the probit modeling was used. The hypothesis of the article is the statement that the innovation of companies will grow after establishing cooperation with business support institutions, while its level will be bigger when the level of manufacturing technique used by the companies is bigger.